Keanekaragaman Tumbuhan Paku di Kawasan Aliran Mata Air Panas Jaboi Kecamatan Sukajaya Kota Sabang - Sy Almunawarah; Muslich Hidayat; Lina Rahmawati; Eriawati Eriawati; Nurdin Amin; Syahrul Rahmanda (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Biodiversity is essentially a reflection of the number of species and individuals inhabiting a community, as seen in the Pteridophyta group. These plants, which have evolved to have differentiated roots, stems, and leaves, play an important role in forest systems, primarily as protectors of the soil surface from the effects of erosion, in addition to contributing to the decomposition of organic matter that produces nutrients, and being a major part of the producer chain in the trophic structure. The Jaboi hot spring area, located in the Sukajaya District of Sabang City, exhibits unique ecological characteristics, influenced by the presence of the Jaboi volcano, which gives rise to geothermal phenomena such as fumarole activity, hot steam emissions, and the emergence of high-temperature water flows. This geothermal dynamic directly causes alterations in the physical and chemical conditions of the local soil, thereby shaping habitat characteristics and influencing the existence of vegetation, including ferns. To date, there is little scientific information available on the diversity of ferns in this area. Therefore, this study was conducted to examine and measure the diversity of ferns in the Jaboi hot spring area. The study was conducted in October 2025 using an exploratory survey approach to determine plots and purposive sampling techniques for field data collection. Diversity analysis was based on the Shannon-Wiener index (Ĥ) formula. Based on the identification results, 15 species of ferns from a total of 6 families and 433 individuals were found. The diversity index obtained (Ĥ=2.490171) indicates a moderate level.